Obsolescence and Art: The canvas and the CRT - Valenzuela, Miguel (La Tadeo Dearte, 2024)
This article proposes that the relationship between obsolescence and art is integral to the way that we conceptualize art and art movements. It looks at the need to reconceptualize the use of CRT television technology in art in the present digital age due to the way that obsolescence has enabled a shift in meaning over two distinct technological eras. Through an analysis of televisual flow and the conceptualization of physical manifestations of television and screen culture, the article argues that the category of obsolete can affect or change the way art is understood or consumed. The importance of this observation relates to theories of use value, perception and design in art and screen culture.